A study of characteristics of female Chinese tourists who participate in New Zealand wine tourism - Huang, Lin (Auckland University of Technology, 2014)
This dissertation deals with female Chinese tourists’ wine behaviour and the role of New Zealand wine tourism. The primary objective of this dissertation is to gain a better understanding of the behaviour of female Chinese tourists in New Zealand wine tourism. This study applies a qualitative methodology to analyse the characteristics of female Chinese tourists in New Zealand wine tourism. Twenty-three ethnic female Chinese tourists over 18 years of age were interviewed about their experiences, attitudes, and behaviours regarding wine consumption while at New Zealand wineries. The respondents were selected at different vineyards and wineries from the Matakana region of Auckland, Waiheke Island vineyards, and the Martinborough Wine trail in Wairarapa in the North Island of New Zealand. All participants described their real wine experiences in New Zealand with their personal feelings and opinions. The purpose of this study is to understand the female Chinese wine tourist and theoretical and practical implications of the behaviour of such tourists for the wine tourism market in New Zealand. The findings from this dissertation show several main influences on female Chinese tourists’ experiences at New Zealand wineries include travelling time, the reputation of wineries, and tour members. From the research perspective, female Chinese tourists appear to visit wineries and vineyards for wine education, leisure with friends, and to experience a different culture during overseas travel. From a practical perspective, this dissertation provides several implications for winery businesses in New Zealand. In particular, the research shows that marketing strategy should focus on different consumer groups from diverse cultural backgrounds and varied consumer behaviours. Different marketing strategies might be needed by different operators in their efforts to better provide for a particular Chinese market.
Keywords: New Zealand wine tourism; Female Chinese